2020
DOI: 10.1093/mnras/staa671
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution spectroscopic study of two new Na- and Al-rich field giants–likely globular cluster escapees in the Galactic halo

Abstract: The stars SDSS J0646+4116 and SDSS J1937+5024 are relatively bright stars that were initially observed as part of the SDSS/MARVELS pre-survey. They were selected, on the basis of their weak CH G-bands, along with a total of 60 others, in the range of halo globular cluster metallicities for high-resolution spectroscopic follow-up as a part of the HESP-GOMPA survey (Hanle Echelle SPectrograph -Galactic survey Of Metal Poor stArs). The stars exhibit typical nucleosynthesis signatures expected from the so-called s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…No trends could be seen for A(Li) with [Na/Fe] (as reported in a few globular clusters), [Ca/Fe] (representative of α-element abundances), [Cr/Fe] (an Fe-peak element), and [Ba/Fe] (an n-capture element). We have also marked the abundances of the globular cluster (GC) escapees (Bandyopadhyay et al 2020b) and the CEMP-no star (Bandyopadhyay et al 2018) with red-filled triangles and pink diamonds, respectively, in each of the panels. Lithium could also be detected for both of the GC escapees of this study, SDSS J064655.6+411620.5 and SDSS J193712.01+502455.5 (Bandyopadhyay et al 2020b), and was found to be normal.…”
Section: Lithium Distribution In the Metal-poor Regimementioning
confidence: 99%
See 1 more Smart Citation
“…No trends could be seen for A(Li) with [Na/Fe] (as reported in a few globular clusters), [Ca/Fe] (representative of α-element abundances), [Cr/Fe] (an Fe-peak element), and [Ba/Fe] (an n-capture element). We have also marked the abundances of the globular cluster (GC) escapees (Bandyopadhyay et al 2020b) and the CEMP-no star (Bandyopadhyay et al 2018) with red-filled triangles and pink diamonds, respectively, in each of the panels. Lithium could also be detected for both of the GC escapees of this study, SDSS J064655.6+411620.5 and SDSS J193712.01+502455.5 (Bandyopadhyay et al 2020b), and was found to be normal.…”
Section: Lithium Distribution In the Metal-poor Regimementioning
confidence: 99%
“…We have also marked the abundances of the globular cluster (GC) escapees (Bandyopadhyay et al 2020b) and the CEMP-no star (Bandyopadhyay et al 2018) with red-filled triangles and pink diamonds, respectively, in each of the panels. Lithium could also be detected for both of the GC escapees of this study, SDSS J064655.6+411620.5 and SDSS J193712.01+502455.5 (Bandyopadhyay et al 2020b), and was found to be normal. Lithium is a fragile element, and is completely destroyed in a temperature range much lower than that required for the operation of the Mg-Al cycle.…”
Section: Lithium Distribution In the Metal-poor Regimementioning
confidence: 99%
“…Stellar parameters were determined using the same methods as described in Bandyopadhyay et al (2018) and Bandyopadhyay et al (2020). Briefly, photometric temperatures were obtained using the available data in the literature and the standard T eff -color relations derived by Alonso et al (1996) and Alonso et al (1999).…”
Section: Observations and Analysismentioning
confidence: 99%